2017
DOI: 10.1108/pr-01-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Perceived employability of Hong Kong employees: its antecedents, moderator and outcomes

Abstract: Purpose The purpose of this paper is to develop and test a model that investigates volition and self-efficacy as antecedents, and work engagement and job satisfaction as outcomes of perceived employability. It also evaluates the moderating role of job insecurity on the relationships between perceived employability and the two employee outcomes. Design/methodology/approach The data were collected via a random sampling survey on living conditions of Hong Kong citizens in 2014. The final sample consists of 414 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 62 publications
6
46
0
1
Order By: Relevance
“…The results showed a significant and positive relationship between employability and well-being, confirming the findings reported by a large number of studies (Berntson & Marklund, 2007;De Cuyper et al, 2008;De Cuyper et al, 2011;De Cuyper et al, 2012;Kirves et al, 2011;Ngo, Liu, & Cheung, 2017). Although these studies have found a positive relationship between employability and well-being, they do not ascribe to theoretical perspectives on which this research is based and also they operationalize the variables in a different way.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results showed a significant and positive relationship between employability and well-being, confirming the findings reported by a large number of studies (Berntson & Marklund, 2007;De Cuyper et al, 2008;De Cuyper et al, 2011;De Cuyper et al, 2012;Kirves et al, 2011;Ngo, Liu, & Cheung, 2017). Although these studies have found a positive relationship between employability and well-being, they do not ascribe to theoretical perspectives on which this research is based and also they operationalize the variables in a different way.…”
Section: Discussionsupporting
confidence: 85%
“…Igualmente, la percepción de discriminación se vinculó negativamente con la empleabilidad, coincidiendo con estudios anteriores que indagan en los posibles efectos de la percepción de trato injusto en el empleo (Noor y Shaker, 2017;Owuamalam y Zagefka, 2014). Los resultados mostraron la existencia de una relación significativa y positiva alta entre la empleabilidad y el bienestar, confirmando los hallazgos reportados por una gran cantidad de estudios (Berntson y Marklund, 2007;De Cuyper et al, 2008;De Cuyper et al, 2011;De Cuyper et al, 2012;Kirves et al, 2011;Ngo et al, 2017) que, si bien han encontrado una relación positiva entre la empleabilidad y el bienestar, no adscriben a las perspectivas teóricas en las que se sustenta esta investigación y han operativizado las variables de diferente manera, por ejemplo, utilizando medidas de empleabilidad percibida, salud mental y satisfacción vital.…”
Section: Discussionunclassified
“…Perceived Employability is considered as an important factor in line with the Job Demands-Resource model (JD-R) (De Cuyper et al, 2011) and Conservation of Resource theory (COR) (Kirves, 2014). Employability perceptions focus on an individual's self-assessment of his/her competency, which is derived from their behavioural competencies skills, knowledge of the labour market, and adaptability (Ngo et al, 2017. Studies indicate that enhanced perceptions of employability could lead to improved job outcomes like improved ability to adapt to changing work environment, job search behaviours, subjective well-being, and health (Berntson, 2008;Chen & Lim, 2012).…”
Section: Protean Career Attitde and Perceived Employabilitymentioning
confidence: 99%
“…In this respect, Kasler et al (2017) reported a significant and positive association between hope, grit and self-perceived employability. Ngo et al (2017) stressed a significant predictive role of general self-efficacy and de Guzman and Choi (2013), the role of career adaptability. Moreover, a longitudinal study conducted by Berntson et al (2008) showed that self-perceived employability and self-efficacy were associated with each another and that self-perceived employability preceded self-efficacy.…”
Section: Perceived Employability and Entrepreneurial Intentionsmentioning
confidence: 99%